Menakar Perilaku Budaya Masyarakat Pesisir Pantai Tanjung Amurang Dalam Menunjang Pengembangan Pariwisata Di Kabupaten Minahasa Selatan - Oktavianus Wayan; Machiko Nugraha Indriyanto (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2021)
The prospect of tourism on the coast of Tanjung Amurang is very promising, but it needs clear efforts, especially the cultural behavior of the local community, to develop it. This study describes the cultural behavior of the people on the coast of the Amurang cape and how this behavior has a major influence on local tourism development. This research will use analytical descriptive methods, including the hermeneutic method as part of the overall description which includes descriptions of several local residents then analyzed. The findings expected in this study are first, the relationship between the cultural behavior of the Tanjung Amurang coastal community with a viewpoint on tourism. Second, get an overview of the situation of the local community in tourism development. Third, the prospect of the local area which can be used as a tourist destination and methods of developing local tourism. The local government of South Minahasa Regency in the preservation of the area around the Tanjung Amurang coast. Fifth, the principles of tourism development as the foundation for future commodities.